Transarterial chemoembolization for advanced hepatocellular carcinoma without macrovascular invasion or extrahepatic metastasis: analysis of factors prognostic of clinical outcomes - Kim, Ji Hoon; Kim, Jin Hyoung; Yoon, Hyun-Ki; Ko, Gi-Young; Shin, Ji Hoon; Gwon, Dong Il; Ko, Heung-Kyu; Chu, Hee Ho; Kim, Seong Ho; Kim, Gun Ha; Kim, Yonghun; Aljerdah, Shakir (Frontiers in Oncology, 2023)
Objectives To evaluate the safety and efficacy of TACE and factors predicting survival in patients with advanced hepatocellular carcinoma (HCC) without macrovascular invasion (MVI) or extrahepatic spread (EHS). Methods This single-center retrospective study included 236 treatment-naïve patients who underwent TACE as first-line treatment for advanced HCC without MVI or EHS between January 2007 and December 2021. Results Following TACE, the median overall survival (OS) was 24 months. Multivariate Cox regression analyses revealed that tumor number ≥4 (risk point: 3), maximal tumor size >10 cm (risk point: 2), Child–Pugh class B (risk point: 2), alpha-fetoprotein (AFP) concentration ≥400 ng/mL (risk point: 2), and presence of HCC rupture (risk point: 2) were risk factors significantly associated with OS. The expected median OS among patients with <2, 2–4, and 5–9 risk points were 72, 29, and 12 months respectively. The major complication rates were significantly lower in patients with maximal tumor size ≤10 cm than in those with maximal tumor size >10 cm (4% [5/138] vs 21% [21/98], p = 0.001). Conclusion TACE may be safe and effective in selected patients with advanced HCC without MVI or EHS, with a median OS of 24 months. Patients with limited tumor burden, compensated liver function, absence of HCC rupture, and favorable biologic markers may benefit the most from TACE. TACE is not recommended for patients with huge HCCs (>10 cm) because of its high rate of major complications (21%).